Influence of reaction parameters on the structure of in situ rubber/silica compounds synthesized via sol–gel reaction. Issue 14 (3rd June 2014) - Miloskovska, Elena; Nies, Erik; Hristova‐Bogaerds, Denka; van Duin, Martin; de With, Gijsbertus
ABSTRACT In situ silica was synthesized in three non‐vulcanized rubber matrices, namely natural rubber, styrene‐butadiene rubber, and EPDM (ethylene‐propylene diene ter‐polymer), using the sol–gel method with tetra‐ethoxysilane (TEOS) as silica precursor and hexylamine as catalyst. The effect of the reaction parameters such as the amount of TEOS, the reaction time (15–120 min), and the type of rubber was explored. Transmission electron microscopy was used to study the gradient in silica content and particle size over the sample thickness. The diffusion gradient of TEOS and catalyst solution in the rubber matrix responsible for the gradient was studied with Fick's law. An excellent dispersion of silica was obtained for all rubbers, even for the very non‐polar EPDM, without the use of any additives to improve the dispersion. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 967–978